Інноваційні педагогічні технології у викладанні професійно орієнтованих дисциплін - Пономарьов, Олександр Семенович; Резнік, Світлана Миколаївна; Асєєва, Ірина Володимирівна; Кравцова, Наталія Вікторівна (Класичний приватний університет, 2016)
The article deals with the application of innovative pedagogical technologies in the training of future bachelors of mechanical-engineering specialties in the higher technical school. Improving the quality of specialists’ training requires a search for effective ways of formation in students the system of ideas about their future careers and skills, organization and management. The effectiveness of training is directly dependent on the level of activity of students. One of the main objectives of the professional training of future specialists is not only the accumulation of knowledge and skills, but also the ability to apply them in practice, the development of cognitive and creative interests, and the desire for selfeducation. There fore, it is necessary to pay attention to the use of innovative pedagogical technologies in teaching of general engineering disciplines that are part of the training. It has been shown that for the development of informative activity of the future bachelors, new forms and methods of cognitive activities that develop creative abilities and form the system of values of the individual should be included in the educational process. When creating didactic and psychological conditions they will contribute to the demonstration of students’ activity. In the process of studying this problem, features and effectiveness of the use of interactive teaching methods in the teaching of general engineering disciplines were shown that can contribute to the effective assimilation of knowledge, improvement of cognitive activity that will allow making professional decisions. Systemic and consistent application of modern innovative pedagogical technologies in teaching of general engineering disciplines can significantly increase the level of training of mechanical-engineering specialties.
The Use of Innovative Pedagogical Technologies in Teaching Engineering Disciplines
Keywords: вища професійна освіта; інноваційні педагогічні технології; інтеравктивні методи навчання; професійно-орієнтовані дисципліни; бакалаври; машинобудівні спеціальності; higher professional education; innovative pedagogical technologies; interactive learning methods; general engineering discipline; bachelors of mechanical engineering specialties